Geomorphology of the northwestern Kurdistan Region of Iraq: landscapes of the Zagros Mountains drained by the Tigris and Great Zab Rivers. Issue 2 (1st December 2021) - Forti, Luca; Perego, Alessandro; Brandolini, Filippo; Mariani, Guido S.; Zebari, Mjahid; Nicoll, Kathleen; Regattieri, Eleonora; Barbaro, Cecilia Conati; Bonacossi, Daniele Morandi; Qasim, Hasan Ahmed; Cremaschi, Mauro; Zerboni, Andrea
ABSTRACT: We present the geomorphological map of the northwestern part of the Kurdistan Region of Iraq, where the landscape expresses the tectonic activity associated with the Arabia-Eurasia convergence and Neogene climate change. These processes influenced the evolution of landforms and fluvial pathways, where major rivers Tigris, Khabur, and Great Zab incise the landscape of Northeastern Mesopotamia Anticlinal ridges and syncline trough compose the Zagros orogen. The development of water and wind gaps, slope, and karsts processes in the highlands and the tilting of fluvial terraces in the flat areas are the main evidence of the relationship between tectonics, climate variations and geomorphological processes. During the Quaternary, especially after the Last Glacial Maximum, fluctuating arid and wet periods also influenced local landforms and fluvial patterns of the area. Finally, the intensified Holocene human occupation and agricultural activities during the passage to more complex societies over time impacted the evolution of the landscape in this part of Mesopotamia.